2008
DOI: 10.1103/physrevlett.101.077202
|View full text |Cite
|
Sign up to set email alerts
|

Self-sustained Magnetoelectric Oscillations in Magnetic Resonant Tunneling Structures

Abstract: The dynamic interplay of transport, electrostatic, and magnetic effects in the resonant tunneling through ferromagnetic quantum wells is theoretically investigated. It is shown that the carrier-mediated magnetic order in the ferromagnetic region not only induces, but also takes part in intrinsic, robust, and sustainable high-frequency current oscillations over a large window of nominally steady bias voltages. This phenomenon could spawn a new class of quantum electronic devices based on ferromagnetic semicondu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…1,2,3,4,5,6,7 Many new device conceptions and functionalities based on these materials are proposed, and the material properties together with the underlying physics are extensively studied. 4,8,9,10,11,12,13,14,15,16 Specifically, ferromagnetic Ga 1−x Mn x As has been used as a highly efficient source to inject spin polarization into GaAs 17 and magnetic tunneling junctions based on ferromagnetic Ga 1−x Mn x As can achieve very high magnetoresistance. 18 Besides, the ability to detect the magnetic moment via Hall measurements 4,19 and to control it via gate-voltage 20 and laser radiation 21 opens the way for incorporating optoelectronics with magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4,5,6,7 Many new device conceptions and functionalities based on these materials are proposed, and the material properties together with the underlying physics are extensively studied. 4,8,9,10,11,12,13,14,15,16 Specifically, ferromagnetic Ga 1−x Mn x As has been used as a highly efficient source to inject spin polarization into GaAs 17 and magnetic tunneling junctions based on ferromagnetic Ga 1−x Mn x As can achieve very high magnetoresistance. 18 Besides, the ability to detect the magnetic moment via Hall measurements 4,19 and to control it via gate-voltage 20 and laser radiation 21 opens the way for incorporating optoelectronics with magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that the exchange splitting of the carriers subbands essentially depends (i) on the spin polarization of the particle density in the well and (ii) on the overlap of the subband wave function with the magnetic impurity density profile. Based on these findings we recently proposed that the combined nonlinear feedback of Coulomb and magnetic interaction can lead to self-sustained high-frequency oscillations of the tunneling current and the quantum well magnetization over a large window of nominally dc-bias voltages [20], as illustrated in the upper panel of Fig. 2.…”
Section: Magnetic Resonant Tunneling Devicesmentioning
confidence: 91%
“…Based on these findings we recently proposed that the combined nonlinear feedback of Coulomb and magnetic interaction can lead to self-sustained high-frequency oscillations of the tunneling current and the quantum well magnetization over a large window of nominally dc-bias voltages [20], as illustrated in the upper panel of Fig. 2.…”
Section: Magnetic Resonant Tunneling Devicesmentioning
confidence: 91%
“…Recently, spin transport through dilute magnetic semiconductor (DMS) diodes 7 and multi‐quantum well structures (MQWS) has been analyzed 8–10, especially the nonlinear features of the current (hysteresis, multistability) as a function of the external voltage. Under strong dc voltage bias V , electric field domains are formed in MQWS due to the interplay between electron–electron interaction and resonant tunneling 8.…”
Section: Introductionmentioning
confidence: 99%